Biomarkers of heart failure: current state of problem - O. P. Ishevskaia; A. M. Namitokov; E. D. Kosmacheva (Инновационная медицина Кубани, 2021)
There is constant increase in patients with heart failure every year worldwide. Early diagnosis and prediction of deterioration could upgrade management of patients and slow down the progression of heart failure.The brain natriuretic peptide precursor (NT-proBNP) is considered to be the universal biomarker, although it has several limitations. The search of ideal biomarker is directed into molecular biology and genetics. Microribonucleic acids (microRNAs) regulate different processes in human body, present myocardial specificity, and plasma stability. It has been proven in different trials that diagnostic and prognostic level of microRNAs is equal to NT-proBNP. Potential opportunities of the method are not only diagnosis but therapeutic targets for heart failure